(untitled) (Argos, 2022)
Abstract: The medieval copyists who had some knowledge of the Greek language limited themselves to trying to reproduce and restore the Greek work and the syntagms contained in the Latin works they were copying, but sometimes they also interpolated and added Greek words. The case of Servius’ commentary is examined in the article, with particular reference to the insular tradition of this text. The investigation enables us to correct some parts of the text of the commentary on the Bucolics published by Thilo.